2017
DOI: 10.1016/j.celrep.2017.11.087
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Changes during Naturally Acquired Zika Virus Infection Render Dendritic Cells Highly Conducive to Viral Replication

Abstract: Summary Although dendritic cells are among the human cell population best equipped for cell-intrinsic antiviral immune defense, they seem highly susceptible to infection with Zika Virus (ZIKV). Using highly-purified myeloid dendritic cells isolated from individuals with naturally-acquired acute infection, we here show that ZIKV induces profound perturbations of transcriptional signatures relative to healthy donors. Interestingly, we noted a remarkable downregulation of antiviral Interferon-stimulated genes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
69
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 50 publications
11
69
1
1
Order By: Relevance
“…Host-virus interaction and its effect on host physiology has so far remained mostly unexplored. Recently, studies based on transcriptomic and proteomic analyses have been instrumental in advancing our understanding of how viruses can affect host physiology (Merkling et al, 2015;Sun et al, 2017;Dong et al, 2017). Our results further emphasize the applicability of such transcriptomic analyses in understanding host-virus interactions and their molecular regulators.…”
Section: Discussionsupporting
confidence: 57%
“…Host-virus interaction and its effect on host physiology has so far remained mostly unexplored. Recently, studies based on transcriptomic and proteomic analyses have been instrumental in advancing our understanding of how viruses can affect host physiology (Merkling et al, 2015;Sun et al, 2017;Dong et al, 2017). Our results further emphasize the applicability of such transcriptomic analyses in understanding host-virus interactions and their molecular regulators.…”
Section: Discussionsupporting
confidence: 57%
“…and interferon-inducible transmembrane proteins (IFITM) family members act as inhibitory factors (Savidis et al, 2016a,b;Meertens et al, 2017;Sun et al, 2017;Van der Hoek et al, 2017;Soto-Acosta et al, 2018). In this study, we identified HCAR2, a G protein-coupled receptor which expression is induced by ZIKV, functions as a restriction factor for ZIKV replication.…”
Section: Discussionmentioning
confidence: 76%
“…Dendritic cells are critical cells which bridge virus detection to activation of antiviral host immunity during natural infection or vaccination. Many viruses, however, have evolved to overcome DC responses; for example, ZIKV infects human DCs and does not cause their activation (64)(65)(66). We explored such ZIKV-DC interactions as a model to define whether increasing of CpG dinucleotides in the RNA viral genome may serve as an approach to subvert impaired antiviral responses in DCs.…”
Section: Immunogenicity and Protective Efficacy Of Cpg-recoded Zikv Vmentioning
confidence: 99%